Diagnosis of neonatal chlamydial conjunctivitis. Issue 8 (August 1990) - Phillips, G; Forsyth, J S; Harper, I A
Abstract : Fifty seven babies with ophthalmia neonatorum had conjunctival smears examined by microscopy and bacterial culture, and by immunofluorescence, to find out which was the best method of diagnosing chlamydial conjunctivitis. The positive (33%) and negative (70%) predictive values of microscopy and culture were too low for us to accept it as an adequate method of detecting the presence of Chlamydia trachomatis.